Effect of Various Stages of Shifting Cultivation on Soil Erosion from Steep Hill Slopes - Singh, Avtar; Singh, M. D. (Indian Forester, 1980)
Soil erosion on Hill slopes (50-60 %) under first year jhurn, record year jhurn and abandoned jhurn and natural bamboo forest has been estimated as 146.6, 179.2, 30.3 8.2 c/hr respectively. Second year cropping in jhurn land have been found comparatively more hazardous than first year. It has been emphasized that to save precious forest wealth, it would be necessary to do away with the jhurn cultivation and adopt alternative conservation based farming system in North Eastern Hills Region.